Morphologic and immune-histochemic peculiarities of placenta in its dysfunction in anemia of pregnancy. - I. A. Ancheva (Medičnì Perspektivi, 2014)
Placental dysfunction occurs in 17-35% of pregnant women. Iron deficiency anemia complicating pregnancy and childbirth affects fetal development. In its turn, pregnancy contributes to the rapid progress of iron deficiency anemia. The aim of the study was to evaluate the morphological and immunohistochemical features of the placenta in its dysfunction in women with anemia during pregnancy. The study was performed on clinical bases of the Department of Obstetrics and Gynecology №1 of ONMedU (Odessa) and pathologic department of SI " IPOG NAMSU" (Kiev). The complex dynamic examination of pregnant women with subsequent examination of the placenta was performed. Patients were divided into 3 groups. 1st group consisted of pregnant women with physiological pregnancy and childbirth (n=10), 2nd group included women suffering from anemia during pregnancy (n=10); 3rd group consisted of women with pregnancy accompanied with placental dysfunction and anemia (n=10). Organometric, macroscopic, general histological, micrometer, histochemical and immunohistochemical methods were used. It is shown that reduction of incidence of regeneration - proliferative marker Ki -67 in the nuclei of villous syncytial structure is more pronounced in the development of placental dysfunction against a background of anemia during pregnancy.